2023
DOI: 10.1002/pmrj.13027
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of care models for chronic disease management: A scoping review of systematic reviews

Abstract: ObjectiveTo conduct a scoping review of models of care for chronic disease management to identify potentially effective components for management of chronic traumatic brain injury (TBI).MethodsInformation sources: Systematic searches of three databases (Ovid MEDLINE, Embase, and Cochrane Database of Systematic Reviews) from January 2010 to May 2021. Eligibility criteria: Systematic reviews and meta‐analyses reporting on the effectiveness of the Chronic Care Model (CCM), collaborative/integrated care, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 274 publications
0
1
0
Order By: Relevance
“…Cancer-related lymphedema is an incurable disease requiring sustained patient support and adherence to a chronic disease management model. 24 The criterion standard of lymphedema management is decongestive lymphatic therapy, [25][26][27] which aims to educate patients about the condition; decrease affected limb volume and fibrosis; optimize functional status; address body image concerns and improve quality of life; and promote patient engagement and self-management.…”
Section: Managementmentioning
confidence: 99%
“…Cancer-related lymphedema is an incurable disease requiring sustained patient support and adherence to a chronic disease management model. 24 The criterion standard of lymphedema management is decongestive lymphatic therapy, [25][26][27] which aims to educate patients about the condition; decrease affected limb volume and fibrosis; optimize functional status; address body image concerns and improve quality of life; and promote patient engagement and self-management.…”
Section: Managementmentioning
confidence: 99%
“…Le lymphoedème lié au cancer est une maladie incurable qui exige un soutien continu envers le patient et l'adhésion à un modèle de gestion des maladies chroniques 24 . La règle d'or de la prise en charge du lymphoedème est une thérapie lymphatique décongestive [25][26][27] , qui vise à éduquer les patients à propos de cette condition; à réduire le volume et la fibrose du membre affecté; à optimiser l'état fonctionnel; à aborder les préoccupations entourant l'image corporelle et à améliorer la qualité de vie; de même qu'à favoriser l'engagement du patient et son autogestion.…”
Section: Prise En Chargeunclassified
“…A recent report revealed that only three out of five examined PCC factors ( i.e. , communication, emotional support, and goal setting) were correlated with increased patient satisfaction among individuals with schizophrenia[ 26 ], but those PCC elements still constitute a paucity of evidence for traumatic brain injury[ 27 ]. Hence, discussing which PCC elements are critical for diabetes care is highly important.…”
Section: Introductionmentioning
confidence: 99%